Another Piece of the Practice Environment Puzzle: Development and Validation of a Team Virtuousness Instrument. Issue 2 (April 2023) - Varagona, Lynn; Ballard, Nancy; McCartt, Peggy; McEwan, Kevin K.; Knotts, Kimberly
Abstract : The Practice Environment Scale of the Nursing Work Index, a widely used practice environment instrument, does not measure vital coworker interrelations. Team virtuousness measures coworker interrelations, yet the literature lacks a comprehensive instrument built from a theoretical foundation that captures the structure. This study sought to develop a comprehensive measure of team virtuousness built from Aquinas' Virtue Ethics Theory that captures the underlying structure. Subjects included nursing unit staff and master of business administration (MBA) students. A total of 114 items were generated and administered to MBA students. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were run on randomly split halves. Based on analyses, 33 items were subsequently administered to nursing unit staff. EFA and CFA were repeated on randomly split halves; CFA item loadings replicated EFA. Three components emerged from the MBA student data: integrity, α = .96; group benevolence, α = .70; and excellence, α = .91. Two components emerged from the nursing unit data: wisdom, α = .97; and excellence, α = .94. Team virtuousness varied significantly among units and correlated significantly with engagement. The two component instrument, named the Perceived Trustworthiness Indicator, is a comprehensive measure of team virtuousness built from a theoretical framework that captures the underlying structure, demonstrates adequate reliability and validity, and measures coworker interrelations on nursing units. Forgiveness and relational and inner harmony emerged as elements of team virtuousness, broadening understanding.